The impact of active labour market policy on post-unemployment outcomes: Evidence from a social experiment in Denmark - Sylvie Blasco; Michael Rosholm (Institute for the Study of Labor (IZA), 2011)
While job search theory predicts that active labour market policies (ALMPs) can affect post-unemployment outcomes, empirical evaluations investigating transition rates have mostly focused on the impact of ALMPs on exit rates from the current unemployment spell. We use a social experiment, which was conducted in Denmark in 2005-6, to investigate the effects of a dramatic intensification of ALMPs on reemployment stability. We investigate the nature of this impact. We estimate a duration model with lagged duration dependence to separately identify indirect (via shorter unemployment duration) and direct (through a more efficient matching process) effects of ALMPs on subsequent employment duration. We find that overall intensive activation significantly reduces unemployment recurrence for men, but not for women. When we control for dynamic selection into employment and lagged duration dependence, the positive impact of the treatment becomes smaller but remains significant. 80% of the global impact of intensification acts through the direct channel for men.
urn:nbn:de:101:1-201104134341
Keywords: J64; C21; C41; J68; 330; social experiment; labour market policy regime; treatment effect; post-unemployment outcome; duration model; lagged duration dependence; dynamic selection; Arbeitsmarktpolitik; Arbeitslosigkeit; Statistische Bestandsanalyse; Geschlecht; Wirkungsanalyse; Dänemark